Faktor-Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Di Kpp Pratama Pekanbaru Tampan - Purwanto Priatmojo; Adriyanti Agustina Putri; Annie Mustika Putri (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to determine the effect of tax incentives, understanding of taxation and tax services on taxpayer compliance at KPP Pratama Pekanbaru Tampan in 2018-2022. Apart from that, this research is expected to become material for consideration at KPP Pratama to consider tax incentives and provide an understanding of taxation to users and serve tax users well. The method in this study uses quantitative methods. The population in this study is the tax payer users at KPP Pratama Pekanbaru, amounting to 100 respondents. The sampling technique uses purposive sampling, namely the entire sampling is based on the objectives and considerations of the researcher. Data that can be processed using SPSS 26 Software. The results of this study explain that tax incentives, understanding of taxation and tax services partially and simultaneously have a positive and significant effect on taxpayer compliance at KPP Pratama Pekanbaru Tampan in 2018-2022. The magnitude of the influence of tax incentives, understanding of taxation and tax services with an Adjusted R Square value of 83.9%.